Budaya Kerja Dan Disiplin Pengaruhnya Terhadap Kinerja Pegawai Pada KPPBC Tipe Madya Pabean B Medan - Hendrik Paulus Dewantara Hutagalung (Fakultas Ekonomi Dan Bisnis Universitas Tjut Nyak Dhien, 2023)
This research aims to determine the influence of work culture and work discipline on the performance of employees of the Medan Customs and Excise Supervision and Service Office, Type B Medan, partially and simultaneously. The method used is descriptive statistical research with the population being all 110 employees at the Customs and Excise Supervision and Service Office of Customs and Excise Type B, and the sample is the entire population, namely 110 employees. The data used is primary data collected using a questionnaire. Data is processed using SPSS. The results obtained are that both partially and simultaneously the variables of work culture and work discipline have a positive and significant effect on organizational culture with a sig value <0.05.